Antibacterial activities of sponge and coral species collected from Malaysia sea water - Qaralleh, Haitham; Syed Osman Idid, Syed Zahir Idid; Saad, Shahbudin; Darnis, Deny Susanti (2009)
he extracts from seven species of marine sponges and corals collected from Langkawi and Pulau Ular, Cherating were screen for antibacterial activity using disc diffusion method and microdilution method against four tested bacterial (Staphylococcus aureus, Bacillus anthracis, Escherichia coli and Pseudomonas aeruginosa). Overall, 71.4% of the all species surveyed in this study yielded either aqueous or organic extract that were active against at least on bacterium. It was observed that sponges and corals extracted with organic solvents provide stronger antibacterial activity than water extract. The result obtaine showed that the sponges had stronger antibacterial activity tahn the corals species. The Gram-positive bacteria were the most sensitive. The sponge with the voucher number (7S82008) was the most active (inhibition zone 12 mm, MIC 1.5 mg/mL against B. anthracis.